Stress (Tako-tsubo) cardiomyopathy: Review - Hakim Irfan Showkat; Sadaf Anwar; Rajeev Srivastava; JS Sabharwal; Siddharth Saxena; Sudhir Saxena (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
Stress cardiomyopathy, also referred to as Takotsubo cardiomyopathy, is an increasingly recognized clinical syndrome characterized by acute reversible apical ventricular dysfunction. Stress cardiomyopathy, also called apical ballooning syndrome, broken heart syndrome, takotsubo cardiomyopathy, and stress-induced cardiomyopathy, is generally characterized by transient systolic dysfunction of the apical and/or mid segments of the left ventricle that mimics myocardial infarction, but in the absence of obstructive coronary artery disease.